Avaliação de receptores hormonais em mulheres com recorrência tardia de câncer de mama: estudo de caso controle - Rigo, Vanessa da Silva (2014)
The breast cancer, the second most common cancer in the world, is the most common among women, accounting for 25% of new cases of cancer each year. Statistics indicate an increase in global incidence. Important changes were signed in the last decade in the modalities of adjuvant and neoadjuvant treatments employed in the management of patients with breast cancer. These modifications include the surgical approach, radiotherapy techniques, chemotherapy agents, the routine use of hormonal therapy and the advent of molecular therapies target. All of them have contributed to the positive impact on survival of patients. In the world population, the median survival after five years is 61% to 85% in developed countries, by estimates of the World Health Organization. An increasing prevalence of women survivors are accompanied in late follow-up. However, even after decades, the risk of disease recurrence is maintained. This risk decreases significantly after the first two years of treatment, but it not annulled after more than a decade of recurrence-free survival of breast cancer. The risk factors and interventions that impact on early recurrence are well known, but it this information is not reproducible for late recurrence risk stratification. In this context, the analysis of hormonal receptors (HR), highlighted, estrogen receptors, is used by be related to the incidence of late recurrence of breast cancer. This study aimed to determine the impact of HR on the late tumor recurrence (RTT). The study consisted of data from all patients with RTT, which began monitoring for breast cancer at the University Hospital of Santa Maria between 2000 and 2009. Therefore were analyzed for cases (21) and controls (42) to obtain data on histology and tumor biology, methods of treatment used, and on the characteristics of RTT. The results demonstrated an increased risk RTT associated with advanced stages (moderate or high) of breast cancer (P = 0.01). However the risk of RTT was not associated with the HR profile (P = 0.61) or overexpression of HER-2 oncoprotein (P = 0.48). Also, it was observed that early recurrence risk reduction of breast cancer, obtained with adjuvant therapy, did not extend to the prevention of RTT, which indicates the need for specific routines to prevent RTT. In conclusion, those patients have a significant risk of RTT, regardless of the HR profile. Overall, these patients are not included in most recent studies involving reduction of late risk.